2016
DOI: 10.1371/journal.pone.0168994
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence and Comparative Genomics of the Novel Lyme Borreliosis Causing Pathogen, Borrelia mayonii

Abstract: Borrelia mayonii, a Borrelia burgdorferi sensu lato (Bbsl) genospecies, was recently identified as a cause of Lyme borreliosis (LB) among patients from the upper midwestern United States. By microscopy and PCR, spirochete/genome loads in infected patients were estimated at 105 to 106 per milliliter of blood. Here, we present the full chromosome and plasmid sequences of two B. mayonii isolates, MN14-1420 and MN14-1539, cultured from blood of two of these patients. Whole genome sequencing and assembly was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…Placing our lipoproteome localization data into the context of genome-and proteome-wide studies may facilitate the identification of additional diagnostic targets and vaccine candidates. The proteomic localization data presented here also provide a predictive framework for proteomic studies of host-pathogen interfaces and envelope structures of other members of the ever-expanding Borrelia genus, including the relapsing fever spirochete Borrelia miyamotoi (136,137) and the recently described North American Lyme disease spirochete Borrelia mayonii (138,139).…”
Section: Discussionmentioning
confidence: 91%
“…Placing our lipoproteome localization data into the context of genome-and proteome-wide studies may facilitate the identification of additional diagnostic targets and vaccine candidates. The proteomic localization data presented here also provide a predictive framework for proteomic studies of host-pathogen interfaces and envelope structures of other members of the ever-expanding Borrelia genus, including the relapsing fever spirochete Borrelia miyamotoi (136,137) and the recently described North American Lyme disease spirochete Borrelia mayonii (138,139).…”
Section: Discussionmentioning
confidence: 91%
“…The closest-related genospecies of the B. burgdorferi s.l. species complex were Borrelia species from North America with B. mayonii, a human pathogenic genospecies recently discovered in the Midwest of the USA [11,12], showing the lowest genetic distance to type strain CA28-91 T (0.040, which equals 96 % similarity) followed by B. burgdorferi s. s. strains Z41293 and B31 (0.042 and 0.045, respectively) and B. americana (0.049) (Fig. 1 and Table S1, available in the online Supplementary Material).…”
Section: Author Affiliationsmentioning
confidence: 99%
“…The authors did state that none of the patients had received antibiotic therapy within the 4 weeks prior to collection of the blood samples. Investigators from the CDC analyzed genetic sequencing data of the isolates said to be recovered using this technique and found that most were not B. burgdorferi sensu stricto [17,18], making the results highly implausible, as infection with Lyme borrelia species other than sensu stricto has not been documented in North America, aside from a very small number of infections due to B. mayonii [19]. The findings of this study were most consistent with laboratory contamination [17,18].…”
mentioning
confidence: 99%